Ecological civilization in the People Republic of China values, action, and future needs. (East Asia working paper., 2019)
Ecological civilization is being used by the Peoples Republic of China to provide a coherent conceptual framework for adjustments to development that meets 21st century challenges. This paper focuses on its significance as a concept, the challenges for applying it widely as a catalyst for reform and progress, and the strategic opportunities for its use in transformative change toward a new relationship between people and nature.